GAS LIFT SPACING DESIGN METHOD FOR UNCONVENTIONAL RESERVOIR WELL - Indira Puspita Sari, Maria
The rapid decline production rate is one of the obstacles to produce well from the unconventional reservoir. Thus, the artificial lift is deployed as the strategy to produce unconventional reservoir economically. Gas lift is favored by the operators due to low cost and flexibility. However, the different characteristics of unconventional reservoir cause the necessity of a different methodology to design gas lift. This study proposes multigradient gas lift design as the novel method to design gas lift valve spacing for the unconventional reservoir. The multigradient gas lift design considers unconventional reservoir transient stage due to the rapid change of rate and pressure during that stage. Several fluid gradients that represent the rate declines are used simultaneously to design gas lift throughout the transient time of the well. The analysis of this study uses the data of well Shale 01 in Delaware Basin from Anadarko Company. The multigradient gas lift design yields less valve than that of conventional for the last stage of the transient time. The results show a reduction of valves to only seven valves which are applicable throughout the transient stage of the well, which leads to no workover requirement, which results in lower cost and shorter downtime. The novelty of multigradient gas lift design method will help the engineers to design gas lift for unconventional reservoir more economically.